A comprehensive study on insecticide poisoning patients brought to a tertiary government hospital in north eastern region of India - Debbarma, Antara; Debbarma, Juthika (Journal of Indian Academy of Forensic Medicine, 2021)
The commonest cause of poisoning in India and other developing countries are insecticide and pesticide, which are agriculturally  based economics, poverty and easy availability. This study collected gastric lavage from all suspected and confirmed insecticide  poisoning cases brought to the hospital. They are being analysed by the thin-layer chromatography method for the detection of the  type of insecticide. This is a cross-sectional study, and statistical analysis is done by correlation and regression analysis method. Total  182 cases of insecticide poisoning were brought to the emergency services of a Government Hospital at Agartala, Tripura, during the  period January 2013 to June 2014, out of which 79.1% were within the age group of 21 years to 40 years, 78.6% of the victims are  male, 50% of the victims were farmers, 98% of the times the mode of poisoning were suicidal, 74% of the cases the insecticide  involved was organophosphorus group of poison (OP), while 19% of the cases were Organochlorine group of poisons (OC), and only  7% of the cases were Carbamate group of poison (CAR). Due to undue pressure for performance and good lifestyle and failure to  comply, the young productive age group tends to take such irreversible steps of committing suicide using easily available material.  The need of the hour is a very restricted supply of insecticides with proper documentation and proper counselling sessions for  survivors of such incidents.
Keywords: Insecticide poisoning; Organophosphorus poisoning; Suicide